Analysis of Management of Village Fund Allocation in Sumberjo Village, Margomulyo District, Bojonegoro Regency - Muhhariawan, Puryadi; Nugroho, Mahendra Adhi (EAJ (Economic and Accounting Journal), 2023)
This study aims to analyze the management of village fund allocation (ADD) in Sumberjo Village, Margomulyo District, Bojonegoro Regency. This research uses a qualitative approach by conducting in-depth interviews and collecting data through field observations and analysis of documents related to ADD management in Sumberjo Village. The collected data was analyzed using a descriptive method to identify the problems and challenges faced in managing ADD and to analyze the effectiveness of using these funds. The results of the study show that the management of ADD in Sumberjo Village faces several problems, including a lack of transparency and accountability in the use of funds, low community participation in making decisions regarding the use of ADD, and limited understanding and capacity of village officials in managing these funds. This research also reveals several efforts made by the village government to improve the management of ADD, such as involving the community in planning and monitoring the use of funds, as well as conducting training and mentoring to increase the capacity of the village apparatus. In improving ADD management in Sumberjo Village, it is recommended that the village government increase the understanding and capacity of the village apparatus in managing these funds and strengthen the monitoring and evaluation mechanisms for the use of ADD. In addition, collaboration with related parties, such as government agencies, communities, and non-governmental organizations, must be increased to support more effective and sustainable management of ADD.